Penerapan Metode Service Quality dalam Melihat Pengaruh Kinerja Pegawai terhadap Kualitas Pelayanan Publik - Effendi, Habiburrahman; Dalimunthe, Ruri Ashari; Saputra, Endra (Building of Informatics, Technology and Science (BITS), 2022)
Public service is a process of bureaucratic performance, the link with bureaucratic culture is very strong, meaning that any activities carried out by public service officers must be guided by the normative rules that have been determined by public organizations as a manifestation of the behavior of public organizations. In this regard, the problem that exists is that the service of public officials at the Pulau Rakyat Sub-district Office, Asahan Regency, shows that there are still deviations in attitudes and behavior as well as the actions of the apparatus as public servants. In everyday reality, it shows that the management services are complicated, require a large amount of money, are less informative or less transparent and discriminatory. In fact, people's expectations for improving the implementation of public services are actually getting further away from the reality. The quality of service is indicated by the absence of professional services, which is the success of the government in managing quality services. The quality of service by the employees of the Pulau Rakyat Sub-district Office of Asahan Regency who are selfish, considerate and serious to carry out their duties and obligations, as well as low knowledge and skills in carrying out their duties